2009
DOI: 10.3233/jad-2009-1114
|View full text |Cite
|
Sign up to set email alerts
|

High Fruit and Vegetable Intake is Positively Correlated with Antioxidant Status and Cognitive Performance in Healthy Subjects

Abstract: A higher daily intake of fruits and vegetables in healthy elderly is associated with an improved antioxidant status in comparison to subjects consuming diets poor in fruits and vegetables, but the impact on cognitive performance is unclear. Healthy community dwellers (45 to 102 years old, n=193) underwent cognitive testing and blood withdrawal for the measurement of antioxidant micronutrients and biomarkers of oxidative stress as well as administration of a food frequency questionnaire to assess the daily inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 33 publications
(41 reference statements)
5
83
3
3
Order By: Relevance
“…The specific protection shown by vegetables and particularly by the green leafy ones appears to be in disagreement with the concept that fruit and vegetable consumption might be beneficial in the frame of a generally healthy lifestyle, as health-conscious individuals tend to consume both fruits and vegetables. A positive association between fruit and vegetable intake, plasma antioxidant micronutrient level and cognitive performance was observed recently in 193 healthy subjects aged 45-102 years (Polidori et al 2009a). In this study, lycopene, a powerful antioxidant carotenoid, was associated with several measures of cognitive performance.…”
Section: Why Should We Care About Diet and Nutrition Against Cognitivsupporting
confidence: 66%
“…The specific protection shown by vegetables and particularly by the green leafy ones appears to be in disagreement with the concept that fruit and vegetable consumption might be beneficial in the frame of a generally healthy lifestyle, as health-conscious individuals tend to consume both fruits and vegetables. A positive association between fruit and vegetable intake, plasma antioxidant micronutrient level and cognitive performance was observed recently in 193 healthy subjects aged 45-102 years (Polidori et al 2009a). In this study, lycopene, a powerful antioxidant carotenoid, was associated with several measures of cognitive performance.…”
Section: Why Should We Care About Diet and Nutrition Against Cognitivsupporting
confidence: 66%
“…With regard to the potential role of lycopene, lutein, and zeaxanthin on AD, previous studies have reported decreased levels in AD patients compared to healthy subjects [25,26,27,40,41,42]. Mecocci et al [25] compared the levels of 8-hydroxy-2′-deoxyguanosine (8-OHdG) and several nonenzymatic antioxidants between elderly AD patients and healthy age- and sex-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…When cognitive function was classified into four levels, participants with the lowest cognitive scores were most likely to have low plasma levels of lycopene and zeaxanthin. In a study by Polidori et al [42], the cognitive score was negatively correlated with blood levels of lycopene and F2 alpha isoprostanes independent of age, gender, BMI, education, total cholesterol, LDL- and HDL-cholesterol, triglycerides, and albumin. Thus, these studies suggested that AD or cognitive impairment as a transitional stage of AD is associated with a poor plasma antioxidant status, increased plasma lipid and protein oxidative modification, and low resistance to peroxyl radical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have shown that high consumption of fruits and vegetables reduces the risk for common causes of death (Lock et al 2005;He et al 2006aHe et al , 2007 and improves cognitive performance in healthy elderly people (Polidori et al 2009;Nurk et al 2010). Previous research from our laboratory, and several others, suggests that the combinations of antioxidant/antiinflammatory phytochemicals found in fruits and vegetables may effectively combat some of the effects of aging [see Miller and Shukitt-Hale (2012) for a review of these studies].…”
Section: Introductionmentioning
confidence: 99%